PERANCANGAN SISTEM PENJADWALAN PIKET SECARA RANDOM DENGAN METODE Hierarchical Model View Controller - zulkifli, ridwan (Universitas Multi Data Palembang, 2024)
The design of random pickup scheduling application is very useful to simplify and speed up the process of making the picket schedule that will be applied to the IT BID Section in West Java Police because nowadays with the rapidly growing technology with the application of this website based hopefully can make the performance on the part of BID IT is increasing. Also through the studies that have been done in the hope can inspire the reader. By using xampp, the application packages that we need in designing a website-based app can work fine, as for the features contained in xampp like ¬apache web server, php, MySQL are available. Not only using xampp application package, but also equipped with CodeIgniter Framework that helps the writer's performance easier in designing and building applications that also includes attendant data, picket data, schedule data and graphics chart to see the implementation of picket every officer. In addition, in the design and construction of this application there are methods HMVC (Hierarchical Model View Controller) to help the performance of making the application to be more structured. Application settings performed by the admin both the process of data security and data confidentiality. All of these are used to hold the necessary data and smoothen the application. Keywords: Application design, picket, random, Website, Polda West Java, CodeIgniter, HMVC (Hierarchical Model View Controller), PHP and MySQL.